The job design happiness scale (JDHS) - Dutschke, G. (2021)
The purpose of this article aims to identify the factors that individuals consider necessary to be happy in their job. Based on these factors, a measure of job design happiness is proposed. Two methods were applied, (1) a qualitative study with content analyses (n=969) to develop an exploratory questionnaire and (2) exploratory and confirmatory factor analysis by applying structural equations models. In this second study the questionnaire was sent to a second sample (n=1079). Five first-order factors were identified: Self-fulfillment; Group Working, Attaining Goals; Leadership and Sustainability and Job/Family Balance. These factors are explained by a second order factor: Job Design Happiness. Further research is needed to determine how the identified ‘job design happiness’ components may interact with one another. Testing the measure of different industries and national cultures is also suggested. Managers and human resources practitioners can improve job and organizational performance by applying the scale in several moments in time measuring the job happiness ‘pulse’, monitoring their decisions. Research on organizational happiness has been increasing but instruments to measure job design happiness, considering organizational factors, are limited.